Teacher Talk and Learner Talk in The Classroom Interaction (An Interaction Analysis to an English Language Class at SMP N 2 Sindang) - Ivon Sagita (Universitas Wiralodra, 2018)
The purpose of this research was to know what teacher talk constitute in classroom interaction, what learner talk constitute in classroom interaction and what percentages of the teacher and learner talk in classroom interaction. The methodology of research used in this research is interaction analysis. An English teacher and whole learners of VII A grade class at SMP N 2 Sindang were chosen as the sample in this research. The class is in the second semester in academic year 2009-2010. In this research the writer applied interview questions for teacher and learners and FIAC (Flanders Interaction Analysis Category). The result of this research showed that teacher more active than learner in the interaction. The teacher generally did most of talking during the lesson. In the available data showed that the teacher used more in indirect influence of FIAC category, they are; accepting feeling, encouragement, accepting or using idea of the learner, and asking question) rather than direct influence (lecturing, giving direction, and criticizing). It is about 49.6% / 16.4 %. Thus the total of teacher talk is 56.4% of the class time. Meanwhile the learners did more response rather than initiation with percentage 30.4% / 12.4% from the total learner talk is 42.8%